Prediction of tacrolimus metabolism and dosage requirements based on CYP3A4 phenotype and CYP3A5*3 genotype in Chinese renal transplant recipients - LUO Xi; ZHU Li-jun; CAI Ning-fang; ZHENG Li-yun; CHENG Ze-neng (Acta Pharmacologica Sinica, 2017)
Aim: To examine how the endogenous CYP3A4 phenotype and CYP3A5*3 genotype of Chinese renal transplant recipients influenced the dose-corrected trough concentration (C0/D) and weight-corrected daily dose (D/W) of tacrolimus. Methods: A total of 101 medically stable kidney transplant recipients were enrolled, and their blood and urine samples were gathered. The endogenous CYP3A4 phenotype was assessed by the ratio of 6β-hydroxycortisol and 6β-hydroxycortisone to cortisol and cortisone in urine. CYP3A5*3 genotype was determined using PCR-RELP. Results: In overall renal transplant recipients, a multiple regression analysis including the endogenous CYP3A4 phenotype, CYP3A5*3 genotype and post-operative period accounted for 60.1% of the variability in C0/D ratio; a regression equation consisting of the endogenous CYP3A4 phenotype, post-operative period, body mass index, CYP3A5*3 genotype, gender, total bilirubin and age explained 61.0% of the variability in D/W ratio. In CYP3A5*3/*3 subjects, a combination of the endogenous CYP3A4 phenotype, postoperative period and age was responsible for 65.3% of the variability in C0/D ratio; a predictive equation including the endogenous CYP3A4 phenotype, post-operative period, body mass index, gender and age explained 61.2% of the variability in the D/W ratio. Base on desired target range of tacrolimus trough concentrations, individual daily dosage regimen was calculated, and all the observed daily doses were within the predicted range. Conclusion: This study provides the equations to predict tacrolimus metabolism and dosage requirements based on the endogenous CYP3A4 phenotype, CYP3A5*3 genotype and other non-genetic variables.